Observational study of left ventricular global longitudinal strain in ST‐segment elevation myocardial infarction patients with extended pharmaco‐invasive strategy: A six months follow‐up study. Issue 2 (19th January 2020) - Manjunath, Satvic C.; Doddaiah, Balaraju; Ananthakrishna, Rajiv; Sastry, Sridhar Lakshmana; Patil, Vikram S.; Devegowda, Lachikrathman; Veervhadraiah, Sumangala B.; bhat, Prabhavathi; Nanjappa Manjunath, Cholenahally
Abstract: Aims and Objectives: To evaluate left ventricular (LV) function by assessment of LV global longitudinal strain (GLS) in ST‐segment elevation myocardial infarction (STEMI) patients who underwent delayed fibrinolysis and coronary intervention (extended pharmaco‐invasive strategy), since LV function is one of the determinants of both immediate and long‐term outcomes. Methods: Prospective study of consecutive STEMI patients who underwent extended pharmaco‐invasive strategy. The LV function was estimated using LV GLS at baseline and at 6 months. Results: The study included eighty‐seven STEMI patients who received delayed pharmaco‐invasive therapy and coronary intervention. The primary aim of the study was to evaluate a change in LV function by assessment of GLS at 6 months as compared to baseline. Prior to PCI, LV ejection fraction was 48.08 ± 6.23% and GLS was −11.11 ± 2.99%. Procedural success was achieved in all patients. LV ejection fraction after 6 months of follow‐up increased to 53.12 ± 5.61% and the GLS improved to −13.03 ± 3.06% In comparison to baseline, there was a significant improvement in both LV ejection fraction and GLS at 6 months of follow‐up ( P < .001).The cardiac mortality was 1.1% at 6 months. Conclusion: There is a significant improvement of LV function as assessed by GLS and ejection fraction at short‐term follow‐up. In a stable cohort of STEMI patients, extended pharmaco‐invasive strategy is also a reasonable option if PCI cannot be performed within the first 24 hours, due to logistic and infrastructural constraints.